Thermophysical Properties of α-Pu2O3: A New Potential Model - Gunay, S. D.; Akgenc, B.; Akdere, U.; Tasseven, C. (AMER INST PHYSICS, 2013)
alpha-Pu2O3 is an important material among plutonium based materials in nuclear industry. Pure plutonium surfaces quickly oxidizes into alpha-Pu2O3 and PuO2 which are in the form of layers one on another [1]. Here we have investigated thermal properties of alpha-Pu2O3 by molecular dynamics simulation by using a partially ionic semi-empirical rigid ion potential. Mechanical properties, thermal expansion, and heat capacity are calculated. Results were compared with available experimental data and quantum calculation [2]. Due to the experimental limitations such as toxicity and radiation effects, studying the physical properties of such materials from molecular dynamics simulations have vital importance.
Keywords: alpha-Pt2O3; molecular dynamics simulation; beta-Pu2O3; lattice constant; elastic modulus; bulk modulus; coordiantion number; Materials Science; Physics